Cholesterol chemistry, biochemistry, and pathology. - Cook, Robert P. (Academic Press, 1958)
Cholesterol: Chemistry, Biochemistry, and Pathology focuses on the properties, characteristics, compositions, and reactions of cholesterol. The selection first offers information on the history of cholesterol, including occurrence of cholesterol, early chemistry, related compounds, and analytical methods. The text then surveys the chemistry of cholesterol; methods of isolation and estimation of sterols; and distribution of sterols in organisms and in tissues. Discussions focus on quantitative determination of sterols, isolation procedures, distribution in animal tissues, sterols in plants, an.